Food‐dependent NSAID‐induced hypersensitivity (FDNIH) reactions: Unraveling the clinical features and risk factors. Issue 5 (22nd December 2020) - Sánchez‐López, Jaime; Araujo, Giovanna; Cardona, Victoria; García‐Moral, Alba; Casas‐Saucedo, Rocío; Guilarte, Mar; Torres, María José; Doña, Inmaculada; Picado, Cesar; Pascal, Mariona; Muñoz‐Cano, Rosa; Bartra, Joan
Abstract: Background: In up to 70%–80% of patients with a suspected non‐steroidal anti‐inflammatory drug hypersensitivity (NSAIDH), challenge tests with the culprit drug yield negative results. On the other hand, there could be a NSAIDH overdiagnosis when anaphylaxis is the clinical manifestation. We hypothesize that some negative NSAID challenge tests and an overdiagnosis of NSAIDH occur in patients with food‐dependent NSAID‐induced hypersensitivity (FDNIH). Methods: We studied 328 patients with a suspected acute NSAIDH. FDNIH was diagnosed in patients meeting all the following: (1) tolerance to the food ingested more temporally closed before the reaction, later the episode, (2) respiratory or cutaneous symptoms or anaphylaxis related to NSAID, (3) positive skin prick test to foods and/or specific IgE to food allergens (Pru p 3, Tri a 19, Pen a 1) involved in the reaction, and (4) negative oral provocation test to the culprit NSAID. Results: 199 patients (60%) were diagnosed with NSAIDH and 52 (16%) with FDNIH. Pru p 3 was involved in 44 cases (84.6%) and Tri a 19 in 6 cases (11%). FDNIH subjects were younger ( p < .001), with a higher prevalence of rhinitis ( p < .001) and previous food allergy ( p < .001), together with a higher proportion of subjects sensitized to pollens ( p < .001) and foods ( p < .001). Using just four variables (Pru p 3 sensitization, Tri a 19 sensitization, anaphylaxis, and any NSAID different from pyrazolones), 95.3% of cases were correctly classified, with a sensitivity of 92% and specificity of 96%. Conclusion: Evaluation of FDNIH should be included in the diagnostic workup of NSAIDH. Abstract : 16% of patients with suspicion of acute NSAID hypersensitivity were diagnosed as FDNIH reactions being lipid transfer protein (Pru p 3) the main food allergen involved. With four variables (Pru p 3 or Tri a 19 sensitization, anaphylactic reaction and any NSAID involved different from a pyrazolone), FDNIH is correctly diagnosed in 95.3% of cases (92% of sensitivity, 96% of specificity). These observations support the relevance of individualized assessment of both NSAID hypersensitivity and food allergy in patients with suspected acute NSAID hypersensitivity. Abbreviations: FDNIH, food‐dependent NSAID‐Induced hypersensitivity; NSAID, non‐steroidal anti‐inflammatory drug